KAJIAN ESTETIKA PERTUNJUKAN WAYANG KULIT LAKON SALYA BEGAL SAJIAN PURBO ASMORO - S., Sugimo; S., Soetarno (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2015)
This research was to gain an understanding of the form of the performance of the story SalyaBegal, the values it contained, and the treatment of the various elements of the performance ofSalya Begal by Purbo Asmoro. The study used an analytical descriptive method and an approachbased on the aesthetics of the art of puppetry. The data was collected through indirect observation, a bibliographical study and interviews. The results of the research showed that the form ofthe performance of Salya Begal by Purbo Asmoro was a condensed performance of shadowpuppet theatre, containing the essence of the story which carried weight and depth of meaning.The values contained in the story of Salya Begal include: loyalty, affection, heroism, humanitarianism, harmony, and justice. The arrangement and treatment of the performance of SalyaBegal not only paid attention to its visual or entertainment aspects but also placed strongemphasis on its important spiritual values, while at the same time taking careful consideration ofits aesthetical values. Hence, it can be said that the aesthetical values found in the treatment ofdialogue in Purbo Asmoro’s performance of Salya Begal contain messages which can enrichspiritual experiences, broaden perceptions, and increase human pride and dignity, which in turnwill bring greater stability to people’s lives.Keywords: aesthetical values, Salya Begal.